A practical method to account for seal friction in aircraft hydraulic actuator preliminary design - Agarwal, Naresh K.; Lawson, Craig P. (SAGE, 2016)
Seals are used in hydraulic actuators or any other hydraulic devices to prevent passing of hydraulic fluid from one chamber to another, or to prevent external leakage and entry of any foreign contaminants. The primary function of any hydraulic actuator is to efficiently use hydraulic power to drive a load experienced during movement of control surfaces or movable aircraft structure. Efficient sealing helps in achieving this, but with its own friction which should be as minimal as possible. Thus, the estimation of seal friction force has crucial significance in hydraulic actuators, especially in flight control actuators that demand high performance and dynamic behavior characteristics while efficiently driving the load. This paper details the methodology adopted for theoretical estimation of total seal friction force of actuator as well as description of experimental test set-up and test method followed to record the total friction value at different positions of the actuator. The theoretical estimation was done using empirical formulae and graphs for predicting seal friction force by considering the effects of seal squeeze, hydraulic pressure, seal dimensions, seal material and then interpolating the same for the specific type of seals used. An experimental study is also presented in this paper, which can be conducted to validate the theoretically estimated value after building up of development prototypes. The validation is necessary as seal friction force calculation during design phase is an approximation and accurate friction of every seal is difficult to measure as it depends on a number of parameters. Thus, this paper explains the subject issue with the help of a case study which provides the theoretical estimation as well as its validation through an experiment to study this significant aspect of a hydraulic actuator design.
Keywords: Actuator effort; Ener-cap; Friction; Hydraulic pressure; Hydraulic seal; Stall load